Gastronomy, Sustainability and Tourism in Caçandoca of Ubatuba ( São Paulo-Brazil) - Maranhão, Ricardo Frota de Albuquerque; Bueno, Marielys Siqueira (Revista Turismo em Análise, 2012)
The beach named Caçandoca, in Ubatuba, has an artisan fishing's community who is alsoremainder of a "quilombo". Since the opening of roads allowed access to the north coastlandof São Paulo, on the seventies, the community have suffered a lot of pressures from theimmovable speculation for her evacuation or removing, because of the natural beauty of the place and its possible touristic utilization. But she obtained the recognition of the territory's property, as a "quilombo's" land, and nowadays she searchs to conserve her identity and her material culture. An important part of this culture is her fishing cookery, approachedby the A. in opening interviews with old dwellers of Caçandoca. And, at the present time, community's and governmental's projects offer alternative possibilitys to make good use ofthis traditional cookery in a sustainable tourism acivity.